2013
DOI: 10.5761/atcs.oa.11.01875
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine: A New Alternative Agent for the Management of the Postoperative Air Leak

Abstract: Purpose: To evaluate the efficacy of taurolidine instillation on postoperative air leak by clinical study and to investigate the mechanism of action by animal experiments. Methods: Outcomes of taurolidine instillation in patients with postoperative air leak were retrospectively reviewed. 100 ml of 1% taurolidine solution was instilled through a chest tube in patients with postoperative air leak lasting 4days or more. Success was defined as cessation of air leak within 24 hours with full expansion of lung on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For these reasons, many investigators have been trying to search for new agents for pleurodesis. Byun et al studied effectiveness of taurolidine, and proposed it is an efficacious alternative agent for the management of PAL (20). Godazandeh et al suggested that iodopovidone is an effective, inexpensive, safe material for chemical pleurodesis in the treatment of malignant pleural effusion and intractable pneumothorax (21).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, many investigators have been trying to search for new agents for pleurodesis. Byun et al studied effectiveness of taurolidine, and proposed it is an efficacious alternative agent for the management of PAL (20). Godazandeh et al suggested that iodopovidone is an effective, inexpensive, safe material for chemical pleurodesis in the treatment of malignant pleural effusion and intractable pneumothorax (21).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, several investigations to search for new agents for pleurodesis are ongoing. Byun et al researched effects of taurolidine and proposed that it is an effective alternative agent for the management of pulmonary air leakage [ 19 ]. Godazandeh et al and other researchers suggested that povidone-iodine is an effective, inexpensive, safe and feasible agent for chemical pleurodesis in the management of malignant pleural effusion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, several investigations to search for new agents for pleurodesis are ongoing. Byun et al researched effects of taurolidine and proposed that it is an effective alternative agent for the management of pulmonary air leakage [19]. Godazandeh et al and other researchers suggested that povidone-iodine is an effective, inexpensive, safe and feasible agent for chemical pleurodesis in the management of malignant pleural effusion [20].…”
Section: Discussionmentioning
confidence: 99%